2014
DOI: 10.7717/peerj.272
|View full text |Cite
|
Sign up to set email alerts
|

Smoking close to others and butt littering at bus stops: pilot observational study

Abstract: Background. Transportation settings such as bus stops and train station platforms are increasingly the target for new smokefree legislation. Relevant issues include secondhand smoke exposure, nuisance, litter, fire risks and the normalization of smoking. We therefore aimed to pilot study aspects of smoking behavior and butt disposal at bus stops.Methods. Systematic observation of smoking and butt disposal by smokers at bus stops. The selection of 11 sites was a mix of convenience and purposeful (bus stops on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Previous studies conducted in Spain, [13] and also in other countries, [8,19,20] showed that smoking was most reported in bars and restaurants in comparison to other outdoor places. Furthermore, public transportation stops were places where we also observed visibility of smokers in accordance to other international studies, [17,37] and should be considered in future interventions. This approach has been adopted in setting such as Queensland, Australia, where smoking is banned within 5 metres of public transportation waiting areas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies conducted in Spain, [13] and also in other countries, [8,19,20] showed that smoking was most reported in bars and restaurants in comparison to other outdoor places. Furthermore, public transportation stops were places where we also observed visibility of smokers in accordance to other international studies, [17,37] and should be considered in future interventions. This approach has been adopted in setting such as Queensland, Australia, where smoking is banned within 5 metres of public transportation waiting areas.…”
Section: Discussionsupporting
confidence: 90%
“…[6] Since the implementation of indoor smoking bans over the past 10-15 years, there has been a focus on examining specific outdoor public spaces where smokers may have relocated, including: outdoor areas of hospitality venues (i.e. bars, restaurants, and cafeterias); [9][10][11] entrances to healthcare centres; [12] surrounding areas of schools and university campuses; [13,14] parks and beaches; [15] playgrounds; [16] public transportation stops; [17] or entrances to other public buildings (e.g. shopping centres, government buildings, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, around 5 trillion cigarette butts are generated per year (Novotny and Zhao 1999, Chapman 2006, Healton et al 2011, Bonanomi et al 2015. Cigarette butts are some of the most common forms of litter found on beaches (Claereboudt 2004, Smith et al 2014, near streams, night clubs (Becherucci and Pon 2014), bus stops (Wilson et al 2014), roads and streets (Healton et al 2011, Patel et al 2013. Cigarette butts have been found at densities averaging more than four cigarette butts m -2 in urban environments (Seco Pon and Becherucci 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These cigarette butts can persist in the environment for more than 18 months (Novotny and Zhao 1999). Cigarette butts are some of the most common forms of litter found on beaches (Claereboudt 2004, Smith et al 2014, near streams, night clubs (Becherucci and Pon 2014), bus stops (Wilson et al 2014), roads and streets (Healton et al 2011, Patel et al 2013. Cigarette butts have been found at densities averaging more than 4 butts m -2 in urban environments (Figure 1.1) (Seco Pon and Becherucci 2012).…”
Section: Introductionmentioning
confidence: 99%